A causal association between amyotrophic lateral sclerosis and atrial fibrillation: a two-sample Mendelian randomization study - Yao, Yiren; Liu, Hongyang; Gu, Yang; Xu, Xiaojin; Zhang, Xiwen (Frontiers in Cardiovascular Medicine, 2024)
Objectives To look into the connection between amyotrophic lateral sclerosis (ALS) and atrial fibrillation (AF) using Mendelian randomization (MR). Methods Two-sample MR was performed using genetic information from genome-wide association studies (GWAS). Genetic variants robustly associated with ALS and AF were used as instrumental variables. GWAS genetic data for ALS (n = 138,086, ncase = 27,205) and AF (n = 1,030,836, ncase = 60,620), publicly available from IEU Open. The specific MR protocols were Inverse variance-weighted (IVW), Simple mode, MR Egger, Weighted mode, and Weight median estimator (WME). Subsequently, the MR-Egger intercept and Cochran Q examine were used to evaluate instrumental variables (IVs)' heterogeneity and multiplicative effects (IVs). In addition, MR-PRESSO analysis was conducted to exclude any potential pleiotropy. Results The IVW method demonstrated that ALS positively affected AF [OR: 1.062, 95% CI (1.004–1.122); P = 0.035]. Indeed, other MR methods were in accordance with the tendency of the IVW method (all OR > 1), and sensitivity testing verified the reliability of this MR result. Conclusions This MR study proves a positive causal connection between ALS and atrial fibrillation. Further studies are warranted to elucidate the mechanisms linking ALS and AF.